2016
DOI: 10.3892/mco.2016.919
|View full text |Cite
|
Sign up to set email alerts
|

A new marker for breast cancer diagnosis, human epididymis protein 4: A preliminary study

Abstract: Breast cancer is the most frequently diagnosed cancer type in women. Tumor markers have been widely used for assessing the treatment response and early diagnosis of recurrence. Human epididymis protein 4 (HE4) is expressed in ductal carcinoma of the breast tissue; however, its serum levels and their diagnostic and prognostic potential in breast cancer have not been investigated, which was therefore the aim of the present study. The serum levels of HE4 were determined in 36 breast cancer patients, 11 ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…Because CA 125 is often elevated in benign conditions or as a result of physiologic changes in premenopausal women, it has not any confirmed role in the early detection of gynecologic cancers. Since abnormal levels of HE4 have been less frequently encountered in benign gynecological conditions HE4 may have increased specificity in differentiating between benign and malignant conditions [2][3][4][5][6][7]. In the present study, we have found that HE4 tissue expression increased in carcinomas, but decreased in intraepithelial neoplasia.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Because CA 125 is often elevated in benign conditions or as a result of physiologic changes in premenopausal women, it has not any confirmed role in the early detection of gynecologic cancers. Since abnormal levels of HE4 have been less frequently encountered in benign gynecological conditions HE4 may have increased specificity in differentiating between benign and malignant conditions [2][3][4][5][6][7]. In the present study, we have found that HE4 tissue expression increased in carcinomas, but decreased in intraepithelial neoplasia.…”
Section: Discussionsupporting
confidence: 64%
“…The potential use of HE4 as a tumor marker has been supported by an increasing number of studies demonstrating an upregulation of HE4 in a range of malignant neoplasms, particularly of gynecological, pulmonary and gastrointestinal origin [3,12,13,16,17,21]. Serological tests have revealed that HE4 has increased sensitivity and specificity in the detection of ovarian cancer relative to CA 125, which is the current gold standard serum biomarker for ovarian carcinomas [3,12]. Several studies examining multiple serum biomarkers for epithelial ovarian carcinomas have found the combination of HE4 and CA125 had greater sensitivity and specificity than either marker alone.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, a large study demonstrated that S-HE4 has a higher sensitivity and specificity in the diagnosis of OC when compared with serum CA-125 (23). However, the evaluation of S-HE4 levels may be problematic when patients suffer from additional conditions, such as CKD (17), heart failure (4), and breast (24) and lung (25) cancer. Thus, the accuracy of S-HE4 in OC diagnosis remains a challenge.…”
Section: Discussionmentioning
confidence: 99%